2022
DOI: 10.3390/cancers14061498
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Checkpoint Inhibitors for Malignant Pleural Mesothelioma: A French, Multicenter, Retrospective Real-World Study

Abstract: Backgrounds: Malignant pleural mesothelioma (MPM) is a cancer with poor prognosis. Second-line and onward therapy has many options, including immune-checkpoint inhibitors with demonstrated efficacy: 10–25% objective response rate (ORR) and 40–70% disease-control rate (DCR) in clinical trials on selected patients. This study evaluated real-life 2L+ nivolumab efficacy in MPM patients and looked for factors predictive of response. Methods: This retrospective study included (September 2017–July 2021) all MPM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…More than half of the studies were reported from the Far East (n = 15) (Ichiki et al, 2019;Jiang et al, 2020;Kitadai et al, 2020;Takada et al, 2020;Ke et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Pu et al, 2021;Sato et al, 2021;Tokuyama et al, 2021;Chen et al, 2022;Kim et al, 2022;Li et al, 2022;Wu et al, 2022;Zhang et al, 2022), followed by Europe (n = 12) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Svaton et al, 2018;Cantini et al, 2020;Awada et al, 2021;Onn et al, 2021;Ruiz-Bañobre et al, 2021;Stares et al, 2021;Assié et al, 2022;Schneider et al, 2022;Stares et al, 2022). A 3.5 gr/dL albumin cut-off was most frequently used in the included studies (n = 20) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Formica et al, 2020;Jiang et al, 2020;Kitadai et al, 2020;Lee et al, 2020;Takada et al, 2020;Awada et al, 2021;Brown et al, 2021;Khaki et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Onn et al, 2021;…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the studies were reported from the Far East (n = 15) (Ichiki et al, 2019;Jiang et al, 2020;Kitadai et al, 2020;Takada et al, 2020;Ke et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Pu et al, 2021;Sato et al, 2021;Tokuyama et al, 2021;Chen et al, 2022;Kim et al, 2022;Li et al, 2022;Wu et al, 2022;Zhang et al, 2022), followed by Europe (n = 12) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Svaton et al, 2018;Cantini et al, 2020;Awada et al, 2021;Onn et al, 2021;Ruiz-Bañobre et al, 2021;Stares et al, 2021;Assié et al, 2022;Schneider et al, 2022;Stares et al, 2022). A 3.5 gr/dL albumin cut-off was most frequently used in the included studies (n = 20) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Formica et al, 2020;Jiang et al, 2020;Kitadai et al, 2020;Lee et al, 2020;Takada et al, 2020;Awada et al, 2021;Brown et al, 2021;Khaki et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Onn et al, 2021;…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thirty-four studies were included in the analyses for OS (Stroup et al, 2000;Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Svaton et al, 2018;Ichiki et al, 2019;Cantini et al, 2020;Formica et al, 2020;Jiang et al, 2020;Kitadai et al, 2020;Lee et al, 2020;Swami et al, 2020;Takada et al, 2020;Awada et al, 2021;Brown et al, 2021;de Kouchkovsky et al, 2021;Ke et al, 2021;Khaki et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Onn et al, 2021;Pu et al, 2021;Ruiz-Bañobre et al, 2021;Sato et al, 2021;Stares et al, 2021;Tokuyama et al, 2021;Abuhelwa et al, 2022;Assié et al, 2022;Chen et al, 2022;Guo et al, 2022;Kim et al, 2022;Li et al, 2022;Stares et al, 2022;Wu et al, 2022;Yoo et al, 2022). In the meta-analysis, patients with lower albumin levels had a significantly increased risk of death (HR: 1.65, 95% CI: 1.52-1.80, p < 0.0001) than patients with higher albumin levels (Figure 1).…”
Section: The Association Between Hypoalbuminemia and Overall Survivalmentioning
confidence: 99%
“…In recent years, related immunological studies have found that immune cell infiltration plays a key role in the tumor microenvironment in the formation, occurrence and development (31,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). The most concerned are the immune checkpoint protein PD-1 and its ligands PD-L1 and PDCD1LG2, tumor transforming growth factor B1 (TGFB1) and its receptors TGFB1R (48)(49)(50)(51)(52)(53)(54). TGFB1 plays an immunosuppressive role in the process of tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia, by acting via increased HIF1α-expression, induces PD-L1 expression in tumor cell lines as well as in murine macrophage and dendritic cells. In MPM, although being related to higher response rates to nivolumab [ 103 , 104 , 105 ], the increased PD1 and PD-L1 expression are mainly associated with sarcomatoid morphology and do not significantly affect overall survival [ 106 , 107 , 108 ]. This observation clearly points out that other parameters are involved with PD1 and PD-L1 in determining real sensitivity to immunotherapy in a complex and heterogeneous context as MPM, such as tumor mutational burden or tumor-infiltrating lymphocytes, the tumor-associated macrophages (TAMs), which are abundantly present in the MPM microenvironment and play an important role in inducing T-cell suppression, Tim-3 (T cell immunoglobulin and mucin-domain containing-3), which is a co-inhibitory receptor expressed on IFN-γ-producing T cells, FoxP3+ Treg cells, and innate immune cells (macrophages and dendritic cells), T-regulatory cells [ 88 , 109 , 110 , 111 , 112 ].…”
Section: The Hypoxia and Stemness Interconnection In Mpmmentioning
confidence: 99%